Description and validation of the Teagasc Lamb Production Model. (October 2016) - Bohan, A.; Shalloo, L.; Malcolm, B.; Ho, C.K.M.; Creighton, P.; Boland, T.M.; McHugh, N.
Abstract: A stochastic budgetary simulation model of a sheep farm was developed to investigate the effects of changes in lamb production systems on farm profitability. Model inputs included: land, labour, capital, animal numbers, as well as, input and output prices. Model outputs were simulated on a monthly basis and included: flock sales and purchases, net energy demand, grass supply and demand, lamb growth and slaughtering pattern, as well as, land and labour utilization. Grass growth, ewe and lamb mortality, fertiliser and concentrate price along with lamb and mutton price were all included in the model as stochastic variables. Farm earnings before interest and tax and net profit, both including and excluding owner/operator labour, were calculated from total receipts from lamb, culled animals and wool less variable and fixed costs. Validation of the model was undertaken by comparing the model outputs to real farm data recorded on 20 Irish commercial sheep farms as well as comparing the model outputs to those of three individual Irish commercial sheep farms. The model outputs were similar to the real farm data indicating that the model provides a realistic representation of actual farm performance, output and profit. To demonstrate potential application of the model, two lambing date scenarios were investigated; a mid-season lambing flock, with a mean lambing date of March 1st and an early lambing flock, with a mean lambing date of January 1st. Both lambing date scenarios had the same farm area, overall herbage utilization, pregnancy scanning rate and number of lambs weaned per ewe joined to the ram, but the early lambing flock had a higher stocking rate (13.23 ewes/ha versus 9.46 ewes/ha for March 1st lambing) which increased due to the higher proportion of concentrate in the total flock diet compared with March 1st lambing. The annual return on investment (ROI) of the mid-season lambing flock was 0.95% with a net profit of €11, 045 excluding owner/operator labour and management. The early lambing system produced a ROI of − 0.70% and a net profit of −€4862. When owner/operator labour and management cost were included the ROI was − 0.38% with net profits of −€5462 for March 1st lambing and a ROI of − 2.46% and net profits of −€26, 735 for January 1st lambing. Highlights: The Teagasc Lamb Production Model (TLPM) can be used to simulate the effect of system changes on farm net profit. Validation of the TLPM showed that the model realistically represented the performance of a typical Irish sheep farm. Date of lambing had a significant effect on farm profit. Early lambing flocks were less profitable than mid-season lambing flocks because of the increased variable costs, most notably feed costs.